The Over-the-Scope Clip System – A Novel Technique for Sastrocutaneous Fistula closure: The first North American Experience - Truptesh H Kothari; Gregory Haber; Niket Sonpal; Nithin Karanth (Canadian Journal of Gastroenterology)
BACKGROUND: The mainstay of therapy for gastrocutaneous (GC) fistulas has been surgical intervention. However, endoclips are currently used for management of perforations and fistulas but are limited by their ability to entrap and hold the tissue.